Non-tropical Cyclone Related Winter Heavy Rainfall Events over the Philippines: Climatology and Mechanisms - Olaguera, Lyndon Mark (Archīum Ateneo, 2020)
This study investigates non-tropical cyclone (TC) related boreal winter heavy rainfall events that lead to extensive flooding (HRF) over the Philippines through a case study and composite analysis. The HRF event examined occurred during January 16– 22, 2017 over Cagayan de Oro City (CDO) in Mindanao Island (122–127°E, 5–10°N). The accumulated rainfall over CDO reached by about 180 mm from 00 UTC January 16 to 00 UTC January 17, 2017, exceeding the climatological maximum daily rainfall in January over this area. The interaction of a westward propagating cyclonic circulation over Mindanao Island (MCC) and a shearline that is associated with an eastward-propagating cyclonic and anticyclonic circulations along 20–40°N, led to enhanced moisture convergence and rainfall over CDO. The climatology of these non-TC related HRF events was examined through composite analysis of the HRF events documented in the Dartmouth Flood Observatory archive from 1979 to 2017. The authors identified 34 of such cases over the Philippines, in which 25 occurred over Mindanao Island. The composites of the circulation features of these 25 cases resemble those during the January 2017 case. A vorticity budget analysis was performed to explain the propagation tendency of the MCC. The results show that the MCC only propagated westward when the magnitudes of the stretching and advection terms of the vorticity tendency equation are almost comparable with each other, together with the weakening of the southerly winds around Mindanao Island. This study reveals how cold fronts over the north Pacific together with the MCC induces HRF events over the Philippines.